Stress Coping Strategies, Burnout, Secondary Traumatic Stress, and Compassion Satisfaction Amongst Israeli Dentists: A Cross-sectional Study - Joseph Meyerson; Marc Gelkopf; Ilana Eli; Nir Uziel (International Dental Journal, 2022)
ABSTRACT: Objective: Being a member of the dental profession is often associated with stress and high levels of burnout. Stress coping strategies may significantly help mediate burnout. The present cross-sectional study sought to examine the role of stress coping strategies on burnout, secondary traumatic stress, and compassion satisfaction amongst Israeli dentists. Methods: The study was carried out amongst Israeli dentists with the use of the following questionnaires: (1) the Professional Quality of Life Scale 5 (ProQOL), referring to burnout, compassion satisfaction, and level of secondary traumatic stress; (2) the Coping Inventory for Stressful Situations–Situation Specific Coping Inventory (CISS-SSC), referring to coping strategies (task-focused, emotion-focused, or avoidance-focused coping); and (3) demographic and professional variables (eg, specialisation, workload). Participants included 243 Israeli dentists. Univariate analyses and linear regressions were conducted to evaluate the relationships amongst coping strategies and burnout, secondary traumatic stress, and compassion satisfaction. Results: Female dentists had higher emotion-focused and avoidance coping scores than male dentists. Burnout could be explained by higher emotion-focused coping scores and lower task-focused and avoidance-focused coping. Secondary traumatic stress could be explained by higher emotion-focused scores, having fewer years of professional experience, and younger ages. Compassion satisfaction could be explained by lower emotion-focused coping as well as by higher task-focused coping and workload scores, specialisation, and gender. Conclusions: The findings suggest that emotional coping may cause dentists to be vulnerable to burnout and to secondary traumatic stress.